Franco-Scottish Architectural Exchanges circa 1535-60 - Ian Campbell (Etudes Epistémè)
The principal argument of the article is that the architecture of the palaces of James V is more eclectic than previously assumed. The advanced French Renaissance character of parts of the Falkland Palace, dating from about 1537-41, is complemented by medieval elements in Falkland, Linlithgow and Stirling, and that this last also has stronger affinities with the buildings of the Habsburg dominions or Portugal than France. It also argues that the Linlithgow plan had a strong influence on the castle of Écouen and on Serlio's Ancy-le-Franc.